Characterizing the Role of Glycogen Synthase Kinase-3α/β in Macrophage Polarization and the Regulation of Pro-Atherogenic Pathways in Cultured Ldlr-/- Macrophages - Patel, Sarvatit; Werstuck, Geoff (Frontiers in Immunology, 2021)
The molecular and cellular mechanisms that link cardiovascular risk factors to the initiation and progression of atherosclerosis are not understood. Recent findings from our laboratory indicate that endoplasmic reticulum (ER) stress signaling through glycogen synthase kinase (GSK)-3α/β induces pro-atherosclerotic pathways. The objective of this study was to define the specific roles of GSK3α and GSK3β in the activation of pro-atherogenic processes in macrophages. Bone marrow derived macrophages (BMDM) were isolated from low-density lipoprotein receptor knockout (Ldlr-/-) mice and Ldlr-/- mice with myeloid deficiency of GSK3α and/or GSK3β. M1 and M2 macrophages were used to examine functions relevant to the development of atherosclerosis, including polarization, inflammatory response, cell viability, lipid accumulation, migration, and metabolism. GSK3α deficiency impairs M1 macrophage polarization, and reduces the inflammatory response and lipid accumulation, but increases macrophage mobility/migration. GSK3β deficiency promotes M1 macrophage polarization, which further increases the inflammatory response and lipid accumulation, but decreases macrophage migration. Macrophages deficient in both GSK3α and GSK3β exhibit increased cell viability, proliferation, and metabolism. These studies begin to delineate the specific roles of GSK3α and GSK3β in macrophage polarization and function. These data suggest that myeloid cell GSK3α signaling regulates M1 macrophage polarization and pro-atherogenic functions to promote atherosclerosis development.